2017
DOI: 10.1038/s41598-017-10962-2
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Membrane Mesenchymal Stem Cells inhibit Neutrophil Extracellular Traps through TSG-6

Abstract: The mesenchymal stem cells obtained from human amniotic membrane (hAMSC) possess immunosuppressive functions through soluble factors such as prostanoids and proteins; thus, they have been proposed to ameliorate inflammatory processes. On the other hand, activated neutrophils are cells of the first line of immune defense that are able to release extracellular traps (NETs). NETs are formed of DNA and granular components; however, the excessive release of NETs is associated with the development of autoimmune and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 72 publications
(72 reference statements)
1
35
0
Order By: Relevance
“…All donors included in this study were 18 years old or older, and the criteria for donation were similar to those reported by Chávez‐García et al . The cells were obtained as previously described, with slight modifications . Briefly, the chorion was separated from the amnion and discarded, while the amnion was incubated with trypsin–EDTA at 37°C to release the amniotic epithelial cells.…”
Section: Methodsmentioning
confidence: 99%
“…All donors included in this study were 18 years old or older, and the criteria for donation were similar to those reported by Chávez‐García et al . The cells were obtained as previously described, with slight modifications . Briefly, the chorion was separated from the amnion and discarded, while the amnion was incubated with trypsin–EDTA at 37°C to release the amniotic epithelial cells.…”
Section: Methodsmentioning
confidence: 99%
“…The mesenchymal stem cells obtained from mesoderm of human amniotic membrane possess immunosuppressive functions through soluble factors such as prostanoids and proteins [34]. AME, an extract of the human amniotic membrane, has also been shown to have anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 TSG-6 in conditioned medium from human AM-derived MSCs was also related to the inflammatory response using LPS-stimulated murine bone marrow-derived neutrophils. 57 Human corneal epithelial cell migration increased significantly with the use of 15% and 30% AMconditioned medium. 58 We observed that AMF-sup had similar effects to AM-sup in this study .…”
Section: Discussionmentioning
confidence: 96%